Estimation of variance components and genetics parameters in a segregating population of tropical maize (Bioagro, 2020)
The estimation of variance components and genetic parameters is useful for directing the selection process in breeding programs. The present investigation was carried out to estimate the components of the genetic variance, average degree of dominance and the heritability for the yield grain and plant traits, in a tropical maize (Zea mays L.) population formed from two lines genetically divergent. One hundred progenies from backcrossing were evaluated in different environments in the municipality Piracicaba, SP, Brazil, in the 2008-2009 and 2009-2010 growing seasons, through an α-lattice design on a factorial scheme with two replications per environment. Estimates of the additive variance, dominance and the additive by environments interaction were significantly different from zero (P≤0.05) for all traits. Estimates of additive variance were significantly (P≤0.05) higher than those of dominance variance for all traits, explaining from 70 to 94% of the total genetic variance. The average degree of dominance ranged from 0.35 (root and stalk lodging) to 0.93 (days to anthesis and days to silk emergence), indicating partial dominance of genes that govern the traits studied. The heritability, at a mean level for all traits, showed high values, ranging from0.58 to 0.96, with a value of 0.94 for the grain yield. The high value of the heritability coefficients implies the possibility of an effective selection for the genetic improvement of grain yield and plant characteristics in the population studied.
Keywords: Degree of dominance; genetic variance; heritability; yield grain; Zea mays